Improving the Computer Forensic Analysis Process through: VISUALIZATION. - Teelink, Sheldon; Erbacher, Robert F. (Communications of the ACM, 2006)
The article reports on improving the computer forensic analysis process through visualization. Computer forensics is the preservation, analysis, and interpretation of computer data. There is a need for software that aids investigators in locating data on hard drives left by persons committing illegal activities. These software tools will reduce the tedious efforts of forensic examiners. The visualization techniques currently provide a novel component for forensic analysis. The ability to display data in a graphical manner significantly enhances the time needed to locate and analyze suspicious files. Visualization techniques can greatly aid forensic specialists to direct their search to suspicious files. Viewing information about multiple files or understanding the relationship between them is also helpful. It allows file searching, pattern matching, and display of file contents. Each of these options allows a deeper analysis of the data stored on the hard drive and results in a flexible and customizable tool for locating criminal evidence.